IMPLEMENTASI STANDAR OPERASIONAL PROSEDUR (SOP) PELAYANAN AKTA KELAHIRAN PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA BENGKULU - Anggriani, Ida; Herfianti, Meiffa (JURNAL EKOMBIS REVIEW, 2017)
The purpose of this research is to know the implementation of SOP (Standard Operational Procedures) for birth certificate services at the Population and Civil Registration Board of Bengkulu City. The method of the data analysis was used is descriptive and qualitative analysis. The study shows that: (1) the preparation phase of the implementation of SOP services at the Population and Civil Registration Board has been executed well, where socialization SOP has been done properly, the SOP has been well implemented and equipment of the Ministry has been drafted and personals, has been shared with the right personnel, so as to facilitate the process of service to the community and (2) the implementation of SOP implementation the issuance of a birth certificate in the Population and Civil Registration Board of Bengkulu City from the stage of receiving and examining the file the petition for a birth certificate, file verification application scheduled, and collect files petition, enter data and print a birth certificate, check, legacy and sign, and submit the quote birth certificate to the community have been implemented in accordance with the stages of service assigned. Every employee involved in the birth certificate service has been implemented in accordance with the stages of service assigned.Keywords: Policy implementation, Standard Operational Procedure; and Birth Certificate